Polymeric seal degradation in nuclear power plants: Effect of gamma radiation on sealing properties. Issue 12 (21st November 2016) - Porter, Christopher P.; Edge, Ruth; Ogden, Mark D.
ABSTRACT: An effort has been made to bridge the gap between academic knowledge of polymeric seal degradation and industrial practices. A series of physical and mechanical properties that can be related to the sealing behavior of three commercial samples of nitrile rubber have been studied for their degradation when exposed to gamma radiation. For all samples the glass transition temperature ( Tg ) and retention factor (RF) were found to increase with total dose whilst percentage change in mass (ΔM% ) was found to decrease. The ultimate uptake of carbon dioxide (CO2 ) did not appear to change with radiation dose but the kinetics of the absorption process were found to decrease, suggesting the formation of crosslinks. The crosslinks formed appear to be dependent on the original material composition and comparison against degradation of material properties supports the theory behind butadiene, BDN, content being linked to a propensity for crosslink clustering. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44618. Abstract :